Ali Al-Misrati’s Satirical Literature Selected Examples from his Short Story Collection “Fifty Short Stories” - Al-Sada’i, Sarah Abdullah Al-Sada’i; bin Khalil, Umm Al-Saad Abdullah Abdul Salam (The annual Scientific Conference for Under and Postgraduate Students at the University., 2024)
Sarcasm is one of the most essential components of the art for the short story. Ali Al-Misrati is considered one of the oldest and most prominent writers of the short story in Libya. Through his satirical literary stories, he was able to, for some extent, to carve a card for himself on the wall of contemporary short story art, with his sarcastic style that became known. With it, Misrati literature formed its own identity and the general template for its works. Al-Misrati believes that the technique of satire is more capable on conveying his literary message, and therefore he preferred it in his narrative literature. This research monitors on the movement of Ali Al-Misrati’s satirical literary story in two aspects: a moral aspect that relates to the general issues that trouble the writer, and believes that it can correct the deviations of the group to which he belongs on several levels, such as the political, social, and moral aspects, and a material aspect that relates to morals, which is physical sarcasm.
Keywords: Short stories; Satire; Ali Al-Misrati; Fifty short stories; Satirical criticism